Perancangan Generator Induksi 1 Fasa Kecepatan Rendah - Prasetyo, Ivan Arif, Agus Supartdi, S.T., M. T., Umar, S.T., M.T (2015)
Induction generator be an alternative option for power generation small power applications in a remote area location. If the induction generator to be applied to a generating system in a remote location, it will be found the fact that the power potential prime movers are used to rotate the generator is not constant. At the micro hydro power plants often found water discharge varies due to the influence of the season. On the other hand, the daily burden to be borne by the generating system is also not constant. These conditions will have a major impact on the voltage and frequency of the power plant. Therefore, it is necessary to do some research to create a prototype of a low-speed induction generator which can generate a voltage and frequency in a small flow of water and different although for implementation in remote areas. Research conducted on the rotational speed of the generator which dikopelkan with an electric motor as the driving switch mounted capacitor bank controller, further testing without the burden of the induction generator excitation 28 μF capacitor with a rotational speed between 770 to 795 RPM and with a 40 μF capacitor excitation with velocity rotate between 700 to 735 RPM. After that, by installing a resistive load measuring 5 Watt to 28 μF capacitor excitation and measuring 5-15 Watt resistive load to 40 μF capacitor excitation on electric installation simple. After testing resumed measure the output of the voltage, frequency and current, then the data is analyzed. Results of research on low-speed generator induksi1 phase with the excitation capacitor 28 μF with resistive load measuring 5 Watt with rotational speed between 793 to 801 RPM obtained a voltage of 71 to 114 volts and a frequency of 52.8 to 53.4 Hz. Subsequent research by the excitation capacitor of 40 μF with rotational speed between 705 to 735 RPM with resistive load measuring 5 Watt obtained a voltage of 84 to 116 volts and a frequency of 48.2 to 49.7 Hz. Furthermore resistive load measuring 10 Watt obtained a voltage of 87 to 105 volts and a frequency of 49.4 to 50.6 Hz. Recent research resistive load measuring 15 Watt obtained a voltage of 77 to 90 volts and a frequency of 50.7 to 51.6 Hz.